Assimilation and Dissimilation in Semitic Languages: Linguistic and Analytical Study - mohi aldeen, basil mohammed (Al-Adab Journal, 2020)
Linguistic sounds represent the scientific aspect of language, and provide common path of communication among the human beings. This communication has resulted in the interest of scholars in the study of linguistic sciences, since ancient times. Those who study Arabic sciences must know the languages ​​of the Semitic Nations for their ancient characteristics and history, because this versedness enriches the linguistic lesson and yields many benefits. The aim of this research is to shed light on the assimilation and the dissimilation in these languages, for its importance in the phonemic lesson. The assimilation is a phonemic harmony between the sounds of the language - in the word- and it is similar in producing the point of sound articulation and sound characteristics. As for the dissimilation, it is a form of substituting the letters of two identical sounds; if one of them is inverted to another sound in order for the dissimilation to occur between the two sounds.